FORMS OF INDEPENDENT WORK IN THE STUDY OF STUDENTS OF GRAPHICAL DISCIPLINES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines forms of extracurricular independent work in studying graphic disciplines. It highlights the role of practical tasks, project work, CAD tools, multimedia, and peer review in developing professional competencies, spatial thinking, and readiness for future teaching.